(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This text discusses the hypothesis of a crisis in theatrical theory in contemporary times by reviewing the main assumptions of some of the critical perspectives of the West, in contrast to recent analytical contributions from new theoretical subjects who socially and temporally situate approaches considered “common”. They formulate cognitive horizons that inscribe in the debate the alterity of their bodies and their voices as theoretical subjects in a territory dialectically configured by the reverse tactics of coloniality hidden in “traditional” theory.